Biotransformations of natural compounds: Structural and functional diversity of novel derivatives - Xanthakis, Epameinondas; Mistriotis, Panagiotis; Stamatis, Haralambos; Magkouta, Sophia; Loutrari, Heleni; Roussos, Charis; Kolisis, Fragiskos N. (My University, 2008)
Phytochemicals, plant compounds with low toxicity and prominent biological actions, are promising candidates for use as functional foods and novel therapeutics. Flavonoids and terpenoids comprise two very interesting classes of phytochemicals as they have been proved effective in prevention and therapy of several cancer types both in vitro and in vivo (Surh, 2003) As chemical heterogeneity among phytochemicals, even within the same class, justifies differences in their action mechanisms, bioavailability and pharmacokinetic profiles, there is a necessity to investigate the structural characteristics that are essential for their biological function. Furthermore, because the use of several bioactive plant compounds is limited by low stability and solubility problems, there is a requirement of improving their physicochemical properties by introducing selective modifications thus extending their application in pharmaceutical and food industry (Srivastava et al., 2005). In these studies, by using enzymatic acylation and/or glucosidation of selected flavonoids (silybin, naringin, rutin) and monoterpenes (perillyl alcohol) in non-conventional reaction systems (Kontogianni et al., 2001) we attempted to investigate their structure-biological activity relationship and also to improve their stability and solubility. We synthesized several novel derivatives which showed compared to parental compounds similar or even increased anti-tumor activities while their physicochemical properties were improved. Our results underline the feasibility of enzymatically producing novel bioactive analogues of phytochemicals displaying desired physicochemical properties. Finally, current research in our laboratory using systemic approaches (genomics, metabolomics) would provide a more global understanding of the mechanisms linked to the anti-tumor actions of the examined phytochemicals and their derivatives.
Keywords: Enzymatic acylation; Structure-biological activity; Solubility